Kontestasi Politik Mantan Terpidana Korupsi dalam Pemilihan Umum (Studi Putusan Mahkamah Agung Nomor 30 P/HUM/2018) - Nova Agustina; Eza Tri Yandy; Sayuti (TANFIDZIY, 2024)
Supreme Court Decision Number 30 P/HUM/2018 decided that Lucianty, an Indonesiam citizen residing in the city of Palembang with the status of a former convict, was declared permittes to nominate as a member of the legislature as a partricipant in the general election for members of the regional representative council. The reason why Lucianty is allowed to run in the general election as a member of the leguslature is because every citizen has the same opportunity to be elected and chose, provided that he must openly state to the public that he is a former convict by showing proof of a letter from the editor-in-chief of local and national mass media. This research is normative juridical research with a case approach. The results of this research show that in the Supreme Court Deciison Number 30 P/HUM/2018 concering Review of Law Number 7 of 2017 concering General Elections against the 1945 Concering General Eletions againts the 1945 Constitution of the Republic of Indonesia, it is true that there is a conflict of interest and violations of human rights.